Overexpression of LAMC2 predicts poor prognosis in colorectal cancer patients and promotes cancer cell proliferation, migration, and invasion - Dandan Huang; Changzheng Du; Dengbo Ji; Jianzhong Xi; Jin Gu (Tumor Biology)
Laminin γ2 (LAMC2) has been reported to be involved in the development and progression of a variety of tumors. However, its function in human colorectal cancer is unclear. Our study aimed to investigate the role of laminin γ2 in colorectal cancer. We first performed the multiple Kaplan–Meier survival analysis of laminin γ2 in a cohort of Gene Expression Omnibus datasets and evaluated its relationship with clinical outcomes of colorectal cancer patients. Then, we established stable colorectal cancer cell lines with laminin γ2 overexpression and examined the functional assays in vitro. Finally the expression pattern of laminin γ2 in colorectal cancer clinical samples was analyzed by immunohistochemistry and quantitative real-time polymerase chain reaction. We found that laminin γ2 was significantly correlated with poor clinical outcomes such as disease-specific, recurrence-free, disease-free, and overall survival in colorectal cancer. Moreover, stably overexpressing laminin γ2 promoted proliferation, migration, and invasion of colorectal cancer cells. In addition, overexpressed laminin γ2 was identified in tumor tissues compared with paired adjacent normal tissues and was related to tumor–node–metastasis stage (p = 0.001) and lymph node metastasis (p < 0.001). In summary, our results strongly suggest that laminin γ2 may be a potential prognostic biomarker and therapeutic target in colorectal cancer.